A thermodynamic-based mixed-integer linear model of post-combustion carbon capture for reliable use in energy system optimisation. (15th April 2023) - Weimann, Lukas; Dubbink, Guus; van der Ham, Louis; Gazzani, Matteo
Abstract: Assessing the role of carbon capture in energy systems dominated by non-dispatchable renewable energy sources requires a reliable and accurate model. However, carbon capture models used in complex systems optimisation are often very simplified. Therefore, we developed a mixed-integer linear model of post-combustion carbon capture starting from rigorous thermodynamic modelling in Aspen Plus. The final model decides the size and the operation of the capture process and returns the cost and energy requirements as a function of the CO2 concentration and the flow rate of the treated flue gas. Validation against actual plant data (Petra Nova) showed excellent accuracy with a deviation in total CO2 captured of just 2%. By applying the model to an exemplary case study, we show that it allows for co-optimising renewables deployment and carbon capture design and operation for a gas turbine, thus opening opportunities to explore new system designs of practical added value. Graphical abstract: Highlights: Mixed-integer linear model of post-combustion carbon capture. Based on Aspen Plus simulations (equilibrium and rate-based). Considers effects of CO2 concentration in the flue gas and part-load behaviour. Dynamic constraints guarantee realistic behaviour in time-resolved analyses. Validation against real plant data shows excellent accuracy (only 2% deviation).